Amblyosyllis, Eusyllis, Odontosyllis, Perkinsyllis and Streptodonta (Annelida: Syllidae) from Brazil, with descriptions of two new species and new records for the country - Paresque, Karla; Fukuda, Marcelo V.; San Martín, Guillermo S.; Nogueira, Joao M. de Matos (Zootaxa, 2015)
We present herein the first records for Amblyosyllis, Eusyllis and Perkinsyllis from northeastern Brazil, describing and illustrating Amblyosyllis sp., Eusyllis kupfferi and E. lamelligera, which are compared to the morphologically most similar congeners; a brief diagnosis is provided for Eusyllis nonatoi, Odontosyllis aracaensis, O. guarauensis, O. guillermoi and Perkinsyllis biota, described from southeastern Brazil. In addition, a new species of Odontosyllis is described, O. brevichaetosa sp. n., characterized by having short, bidentate falciger blades with inverted dorso-ventral gradation in length, and shafts of ventralmost falcigers from midbody parapodia onwards subdistally inflated, with sigmoid tip. A key for the valid Brazilian species of Odontosyllis is provided. Finally, this is also the first account of the genus Streptodonta for the South Atlantic, with the description of S. fauchaldi sp. n., characterized by a distinct distribution pattern of cilia along body, presence of spiniger-like chaetae, and morphology of falciger blades.
World Polychaeta Database (WPolyDb)